PENGARUH PROFITABILITAS, STRUKTUR KEPEMILIKAN, PERTUMBUHAN PERUSAHAAN DAN EFEKTIVITAS USAHA TERHADAP KEBIJAKAN DIVIDEN DI BURSA EFEK INDONESIA - Wahyuni, Rani; Janrosl, Viola Syukrina E (SCIENTIA JOURNAL, 2020)
Dividend policy which contributes to obtain profits obtained by entities that can be distributed to investors as dividends or requested in the form of profits that are used as capital in the future by the entity. In this sduty, there is a purpose to determine the effect of profitability, ownership structure, company growth and business effectiviness on dividend policy in the consumer goods industry sector and miscellaneous industry sector on the Bursa Efek Indonesia. The independent variables used are profitability, ownership structure, company growth and business effectiveness. The population in this study consisted of 109 companies included in the consumer goods industry sector and miscellaneous industry sector on the Bursa Efek Indonesia.samples selected by purposive sampling were selected into 10 companies listed on the Bursa Efek Indonesia in the period 2015-2019. The data collection technique used was documentation technique. Data management technique used is data management with SPSS version 21. Data analysis method used is to use multiple linear methods.